Rapid glacier retreat rates observed in West Antarctica - Milillo, Pietro; Rignot, Eric; Rizzoli, Paola; Scheuchl, Bernd; Mouginot, Jeremie; Bueso Bello, Jose Luis; Prats, Pau; Dini, Luigi (Nature Geoscience, 2022)
The Pope, Smith and Kohler glaciers, in the Amundsen Sea Embayment of West Antarctica, have experienced enhanced ocean-induced ice-shelf melt, glacier acceleration, ice thinning and grounding-line retreat in the past 30 years. Here we present observations of the grounding-line retreat of these glaciers since 2014 using a constellation of interferometric radar satellites combined with precision surface elevation data. We find that the grounding lines develop spatially variable, kilometre-scale, tidally induced migration zones. After correction for tidal effects, we detect a sustained pattern of retreat coincident with high melt rates of ungrounded ice, marked by episodes of more rapid retreat. In 2017, Pope Glacier retreated 3.5 km in 3.6 months, or 11.7 km yr–1. In 2016–2018, Smith West retreated at 2 km yr–1 and Kohler at 1.3 km yr–1. While the retreat slowed in 2018–2020, these retreat rates are faster than anticipated by numerical models on yearly timescales. We hypothesize that the rapid retreat is caused by unrepresented, vigorous ice–ocean interactions acting within newly formed cavities at the ice–ocean boundary.